A transparent self-lubricating anti-icing coating and preparation method thereof
By forming an interpenetrating network structure of acrylate monomer and high-strength resin in the transparent self-lubricating anti-ice coating, the problem that the existing coating is difficult to maintain its function for a long time in harsh environments, and the anti-ice effect with high mechanical strength, good adhesion and excellent transparency is achieved.
Patent Information
- Application Number
- CN202310991410.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-08-08
AI Technical Summary
The existing transparent self-lubricating anti-ice coating is difficult to maintain function for a long time in harsh external environments, and the mechanical strength and transparency are insufficient, which limits its application on wind power blades and photovoltaic power plate surfaces.
By mixing acrylate monomers, acrylate self-lubricating components, initiators and organic solvents, polymerization reaction is carried out to form a self-lubricating resin dispersion, and mixing it with high-strength resin and curing agent to form a transparent self-lubricating anti-ice coating with an interpenetrating network structure.
The prepared transparent self-lubricating anti-ice coating has high mechanical strength, good substrate adhesion and excellent transparency. It can maintain anti-ice performance for a long time and meets the anti-ice needs of substrates such as wind power blades and photovoltaic power plates.
Smart Images

Figure CN116948482B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anti-icing materials, and in particular to a transparent self-lubricating anti-icing coating and a preparation method thereof. Background Art
[0002] Anti-icing technology has attracted attention in many fields. As wind turbines and photovoltaic panels are exposed to the natural environment for a long time, they are greatly affected by the environment and climate. Blade icing is the most important factor affecting the safety and power generation of the unit. Blade icing will cause changes in the blade airfoil, affecting the output of the unit. In severe cases, it will cause the unit to shut down and produce a large power curve deviation, resulting in power loss, and will affect the balance of the impeller, resulting in uneven loads on the blades and transmission components, affecting the service life and operational safety of the unit. For photovoltaic generators, surface ice accumulation will reduce the surface power generation efficiency and even make it impossible to generate electricity.
[0003] Compared with the traditional anti-icing method, namely hot air / electric heating anti-icing, coating anti-icing has an extremely excellent anti-icing effect, does not require energy consumption, is energy-saving and environmentally friendly, and has attracted the attention of researchers. Coating anti-icing is free from the constraints of energy and system, and is considered to be one of the most important components of the new generation of anti-icing system.
[0004] Superhydrophobic surfaces and lubricant-infused surfaces are the most typical passive anti-icing surfaces, which rely on the lotus leaf-inspired solid-air interface and the pitcher plant-inspired solid / liquid interface, respectively. However, poor durability makes it difficult for these surfaces to maintain their functions for a long time in harsh external environments. In addition, the poor mechanical strength and low transparency of such surfaces greatly limit their application in wind blades and photovoltaic panels. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a transparent self-lubricating anti-icing coating and a preparation method thereof. The transparent self-lubricating anti-icing coating prepared by the present invention has high strength and good adhesion to the substrate, and can maintain the anti-icing performance of the interface for a long time, and also has good transparency, which can meet the anti-icing needs of substrates including wind turbine blades and photovoltaic panels.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a transparent self-lubricating anti-icing coating, comprising the following steps:
[0008] (1) mixing an acrylate monomer, an acrylate self-lubricating component, an initiator and an organic solvent to obtain a dispersion;
[0009] (2) heating the dispersion to perform a polymerization reaction to obtain a self-lubricating resin dispersion;
[0010] (3) mixing the self-lubricating resin dispersion with a high-strength resin component and a curing agent to obtain a mixed dispersion;
[0011] (4) coating the mixed dispersion on the surface of a substrate and curing the mixed dispersion to form the transparent self-lubricating anti-icing coating.
[0012] Preferably, the acrylic acid ester monomer in step (1) includes one or more of isobornyl methacrylate, hydroxyethyl methacrylate, isopropenyl acetate, ethyl acrylate, lauryl acrylate, octadecyl acrylate and butyl methacrylate.
[0013] Preferably, in the structure of the acrylic ester self-lubricating component of step (1), the group connected to the oxygen in the ester group is an alkyl group or a fluorine-substituted alkyl group, and the number of carbon atoms of the alkyl group or the fluorine-substituted alkyl group is greater than or equal to 4.
[0014] Preferably, the acrylate self-lubricating component in step (1) includes one or more of 1H,1H,2H,2H-perfluorodecyl acrylate, lauryl methacrylate, octadecyl methacrylate, perfluoropolyether (meth)acrylate and perfluoroalkylethyl acrylate.
[0015] Preferably, the mass of the acrylate self-lubricating component in step (1) is 5-85% of the sum of the mass of the acrylate monomer and the acrylate self-lubricating component; the mass of the initiator is 0.5-5% of the sum of the mass of the acrylate monomer and the acrylate self-lubricating component.
[0016] Preferably, the polymerization reaction temperature in step (2) is 50 to 120° C. and the reaction time is 8 to 12 hours.
[0017] Preferably, the high-strength resin in step (3) comprises one or more of epoxy resin, polydimethylsiloxane, polyurethane and polyurea.
[0018] Preferably, based on the total mass of the acrylate monomer, the acrylate self-lubricating component, the high-strength resin component and the curing agent, the total mass percentage of the acrylate monomer and the acrylate self-lubricating component is 10-90%.
[0019] Preferably, the substrate in step (4) comprises glass, wind turbine blades, photovoltaic panels, epoxy resin boards, metal or wood.
[0020] The present invention provides a transparent self-lubricating anti-icing coating prepared by the preparation method described in the above technical solution, wherein the transparent self-lubricating anti-icing coating comprises a high-strength resin and a self-lubricating resin, and the molecular chains of the high-strength resin and the self-lubricating resin form an interpenetrating network structure.
[0021] The present invention provides a method for preparing a transparent self-lubricating anti-icing coating, comprising the following steps: mixing an acrylate monomer, an acrylate self-lubricating component, an initiator and an organic solvent to obtain a dispersion; heating the dispersion to perform a polymerization reaction to obtain a self-lubricating resin dispersion; mixing the self-lubricating resin dispersion with a high-strength resin and a curing agent to obtain a mixed dispersion; coating the mixed dispersion on a substrate surface, and curing to form the transparent self-lubricating anti-icing coating. In the present invention, the acrylate monomer and the acrylate self-lubricating component are polymerized under the action of an initiator to form a self-lubricating resin; then a high-strength resin component and a curing agent are added to react to form an interpenetrating structure of the high-strength resin and the self-lubricating resin. The present invention constructs a transparent self-lubricating anti-icing coating by interpenetrating low-surface energy self-lubricating polymer chains and high-strength resin segments, wherein the self-lubricating polymer component provides hydrophobic and low ice adhesion properties, and the high-strength resin improves the mechanical strength and wear resistance of the coating. The transparent self-lubricating anti-icing coating prepared by the present invention has high strength and good adhesion to the substrate, and can maintain the anti-icing performance of the interface for a long time. It also has excellent transparency and can meet the anti-icing needs of substrates including wind turbine blades and photovoltaic panels. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic diagram of the structure of the transparent self-lubricating anti-icing coating provided by the present invention;
[0023] Figure 2 This is an optical photograph of the transparent self-lubricating anti-icing coating prepared on the original glass surface in Example 1;
[0024] Figure 3 Transparency data diagram of the transparent self-lubricating anti-icing coating prepared in Examples 1 to 2;
[0025] Figure 4 This is a graph showing the adhesion data between the transparent self-lubricating anti-icing coating prepared in Examples 1 to 2 and the substrate;
[0026] Figure 5 This is a data diagram of the slip angle of the transparent self-lubricating anti-icing coating prepared in Examples 1 to 2;
[0027] Figure 6 This is a graph showing the ice adhesion data of the transparent self-lubricating anti-icing coating prepared in Examples 1 to 2;
[0028] Figure 7 The transparent self-lubricating anti-icing coating surface prepared in Example 1 was abraded 200 times under a load of 250 g, and the change of ice adhesion on the surface before and after abrasion was shown. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a transparent self-lubricating anti-icing coating, comprising the following steps:
[0030] (1) mixing an acrylate monomer, an acrylate self-lubricating component, an initiator and an organic solvent to obtain a dispersion;
[0031] (2) heating the dispersion to perform a polymerization reaction to obtain a self-lubricating resin dispersion;
[0032] (3) mixing the self-lubricating resin dispersion with a high-strength resin component and a curing agent to obtain a mixed dispersion;
[0033] (4) coating the mixed dispersion on the surface of a substrate and curing the mixed dispersion to form the transparent self-lubricating anti-icing coating.
[0034] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known to those skilled in the art.
[0035] The invention mixes acrylate monomers, acrylate self-lubricating components, initiators and organic solvents to obtain a dispersion.
[0036] In the present invention, the acrylic acid ester monomer preferably includes one or more of isobornyl methacrylate, hydroxyethyl methacrylate, isopropenyl acetate, ethyl acrylate, lauryl acrylate, octadecyl acrylate and butyl methacrylate, and is more preferably a mixture of isobornyl methacrylate and hydroxyethyl methacrylate, and the mass ratio of isobornyl methacrylate to hydroxyethyl methacrylate in the mixture is preferably 1:1.
[0037] In the present invention, the group connected to the oxygen in the ester group in the structure of the acrylate self-lubricating component is preferably an alkyl group or a fluorine-substituted alkyl group, and the number of carbon atoms of the alkyl group or the fluorine-substituted alkyl group is preferably greater than or equal to 4. The acrylate self-lubricating component further preferably includes one or more of 1H, 1H, 2H, 2H-perfluorodecyl acrylate, lauryl methacrylate, octadecyl methacrylate, perfluoropolyether (meth) acrylate and perfluoroalkylethyl acrylate, more preferably lauryl methacrylate or a mixture of 1H, 1H, 2H, 2H-perfluorodecyl acrylate and lauryl methacrylate. When the acrylate self-lubricating component is preferably a mixture of 1H, 1H, 2H, 2H-perfluorodecyl acrylate and lauryl methacrylate, the mass ratio of 1H, 1H, 2H, 2H-perfluorodecyl acrylate and lauryl methacrylate in the mixture is preferably 7:3. In the present invention, the acrylate self-lubricating component has hydrophobicity and self-lubricating properties.
[0038] In the present invention, the initiator preferably includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide, and more preferably azobisisobutyronitrile.
[0039] In the present invention, the mass of the acrylic acid ester self-lubricating component is preferably 5 to 85% of the sum of the mass of the acrylic acid ester monomer and the acrylic acid ester self-lubricating component, more preferably 15 to 60%, and further preferably 20 to 50%; the mass of the initiator is preferably 0.5 to 5% of the sum of the mass of the acrylic acid ester monomer and the acrylic acid ester self-lubricating component, more preferably 0.9 to 3%, and further preferably 1 to 2%.
[0040] In the present invention, the organic solvent preferably includes one or more of xylene, toluene, acetone, ethyl acetate and butyl acetate, and more preferably ethyl acetate. The present invention has no particular requirement on the amount of the organic solvent, as long as it can ensure that the components are fully dispersed.
[0041] In the present invention, the acrylate monomer, acrylate self-lubricating component and initiator are preferably added to an organic solvent for mixing; after the mixing, the obtained system is preferably subjected to aeration degassing to obtain the dispersion. In the present invention, the gas used for the aeration degassing is preferably nitrogen or argon, and the aeration degassing is preferably performed under continuous stirring until all the oxygen dissolved in the solution is discharged.
[0042] After obtaining the dispersion, the present invention heats the dispersion to carry out a polymerization reaction to obtain a self-lubricating resin dispersion. In the present invention, the polymerization reaction temperature is preferably 50 to 120°C, more preferably 80 to 100°C, and the polymerization reaction time is preferably 8 to 12 hours, specifically based on the generation of a milky white dispersion; the polymerization reaction is preferably carried out under protective atmosphere conditions, and the protective atmosphere is preferably nitrogen or argon; during the polymerization reaction, the dispersion is preferably kept rotating. During the polymerization reaction, the carbon-carbon double bonds on the acrylate groups in the acrylate monomers and the acrylate self-lubricating components undergo a chain polymerization reaction under the action of an initiator to generate a milky white self-lubricating resin dispersion.
[0043] After obtaining the self-lubricating resin dispersion, the present invention mixes the self-lubricating resin dispersion with a high-strength resin component and a curing agent to obtain a mixed dispersion. Before mixing with the high-strength resin component and the curing agent, the present invention preferably evaporates and concentrates the self-lubricating resin dispersion, and the evaporation and concentration temperature is preferably 25 to 60° C. The degree of evaporation and concentration is based on meeting the use requirements.
[0044] In the present invention, the high-strength resin component preferably includes one or more of epoxy resin, polydimethylsiloxane, polyurethane and polyurea, more preferably polyurea. The present invention has no special requirements for the epoxy resin, polydimethylsiloxane, polyurethane and polyurea, and the corresponding commercial products well known to those skilled in the art can be used; the present invention has no special requirements for the type and amount of the curing agent, and the type and amount of the curing agent well known to those skilled in the art that is compatible with the high-strength resin can be used.
[0045] In the present invention, based on the total mass of the acrylate monomer, the acrylate self-lubricating component, the high-strength resin component and the curing agent, the total mass percentage of the acrylate monomer and the acrylate self-lubricating component is preferably 10 to 90%, more preferably 30 to 80%, and further preferably 50 to 60%.
[0046] The present invention preferably adds the high-strength resin and curing agent into the self-lubricating resin dispersion for mixing. The mixing is preferably stirring. The present invention has no special requirements on the speed and time of the stirring and mixing, as long as the components are mixed evenly.
[0047] After obtaining the mixed dispersion, the present invention applies the mixed dispersion on the surface of the substrate, and after curing, forms the transparent self-lubricating anti-icing coating. In the present invention, the substrate preferably includes glass, wind turbine blades, photovoltaic panels, epoxy resin boards, metals or wood. Before coating, the present invention preferably cleans and dries the substrate, and the cleaning agent used for the cleaning is preferably ethanol, acetone, xylene or water. In the present invention, the coating method is preferably spraying, brushing, rolling, dripping or scraping.
[0048] In the present invention, the curing is preferably room temperature curing or heating curing; the room temperature curing time is preferably 8 to 24 hours, more preferably 12 hours; the heating curing temperature is preferably 60 to 80°C, and the time is preferably 2 to 6 hours. After the curing, the organic solvent is completely volatilized, the coating is fully cross-linked, the high-strength resin component reacts with the curing agent to form a high-strength resin, and interpenetrates with the self-lubricating resin to form the transparent self-lubricating anti-icing coating.
[0049] In the present invention, the thickness of the transparent self-lubricating anti-icing coating is preferably 20 μm to 300 μm.
[0050] The present invention provides a transparent self-lubricating anti-icing coating prepared by the preparation method described in the above technical solution, wherein the transparent self-lubricating anti-icing coating comprises a high-strength resin and a self-lubricating resin, and the high-strength resin and the self-lubricating resin form an interpenetrating network structure. Figure 1The transparent self-lubricating anti-icing coating prepared by the present invention has high strength and good adhesion to the substrate, and can maintain the anti-icing performance of the interface for a long time. It also has excellent transparency and can meet the anti-icing needs of substrates including wind turbine blades and photovoltaic panels.
[0051] In order to further illustrate the present invention, the transparent self-lubricating anti-icing coating and the preparation method thereof provided by the present invention are described in detail below in combination with examples, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] A transparent self-lubricating anti-icing coating for wind turbine blades and photovoltaic panels, the preparation method is as follows:
[0054] (1) adding 5 g of isobornyl methacrylate, 5 g of hydroxyethyl methacrylate, 7 g of 1H,1H,2H,2H-perfluorodecyl acrylate, 3 g of lauryl methacrylate and 0.2 g of azobisisobutyronitrile to 30 g of ethyl acetate, mixing the mixture thoroughly, and degassing with air to obtain a dispersion;
[0055] (2) stirring the dispersion obtained in (1) at 80° C. under a nitrogen inert atmosphere until a milky white self-lubricating resin dispersion is generated;
[0056] (3) evaporating and concentrating the milky white self-lubricating resin dispersion obtained in (2) until the solid content is 80%, adding 10 g of polyurea resin and 10 g of curing agent thereto, and stirring thoroughly to obtain a mixed dispersion;
[0057] (4) The substrates (original glass and glass fiber reinforced epoxy resin board) are cleaned with a cleaning agent and dried respectively; the mixed dispersion obtained in (3) is evenly sprayed on the surface of the substrate, and the sprayed sample is left to stand and cure at room temperature for 12 hours. The coating is fully cross-linked and cured to obtain a transparent self-lubricating anti-icing coating with a thickness of about 200 μm.
[0058] Example 2
[0059] A transparent self-lubricating anti-icing coating for wind turbine blades and photovoltaic panels, the preparation method is as follows:
[0060] (1) adding 5 g of isobornyl methacrylate, 5 g of hydroxyethyl methacrylate, 10 g of lauryl methacrylate and 0.2 g of azobisisobutyronitrile to 30 g of ethyl acetate, mixing thoroughly, and degassing with air to obtain a dispersion;
[0061] (2) stirring the dispersion obtained in (1) at 80° C. under a nitrogen inert atmosphere until a milky white self-lubricating resin dispersion is generated;
[0062] (3) evaporating the white self-lubricating resin dispersion obtained by concentrating the emulsion (2) until the solid content is 80%, adding 20 g of polyurea resin and 20 g of curing agent thereto, stirring thoroughly to obtain a mixed dispersion;
[0063] (4) The substrates (original glass and glass fiber reinforced epoxy resin board) are cleaned with a cleaning agent and dried respectively; the mixed dispersion obtained in (3) is evenly sprayed on the surface of the substrate, and the sprayed sample is left to stand and cure at room temperature for 12 hours. The coating is fully cross-linked and cured to obtain a transparent self-lubricating anti-icing coating with a thickness of about 200 μm.
[0064] Figure 2 This is an optical photograph of the transparent self-lubricating anti-icing coating prepared on the original glass surface in Example 1. Figure 2 The left and right images in the middle are optical photographs of the surface.
[0065] Figure 3 The transparency data of the transparent self-lubricating anti-icing coating prepared in Examples 1 to 2 is shown in FIG. Figure 3 It can be seen that the coatings prepared in Examples 1 and 2 exhibit good transparency. For light with a wavelength of 400 nm to 900 nm, the transmittance of the coating prepared in Example 1 reaches 90%, and the transmittance of the coating prepared in Example 2 reaches 88%.
[0066] Figure 4 The following is a graph showing the adhesion data between the transparent self-lubricating anti-icing coating prepared in Examples 1 and 2 and the substrate (glass fiber reinforced epoxy resin board). Figure 4 It can be seen that the coating in Example 1 exhibited a bonding strength of ˜7.32 MPa with the substrate, and the coating in Example 2 exhibited a bonding strength of ˜6.93 MPa with the substrate.
[0067] Figure 5 is the slip angle data of the transparent self-lubricating anti-icing coating prepared in Examples 1 to 2. Figure 5 It can be seen that the coatings prepared in Examples 1 to 2 have excellent droplet sliding properties, wherein the sliding angle of the coating in Example 1 is 8.6°, and the sliding angle of the coating in Example 2 is 9.4°, indicating that the transparent self-lubricating anti-icing coatings prepared in Examples 1 to 2 have extremely strong liquid repellency.
[0068] Figure 6 1 is a graph showing the ice adhesion data of the transparent self-lubricating anti-icing coating prepared in Examples 1 to 2. Figure 6 It can be seen that the coating prepared in Example 1 has an ice adhesion strength of ~36 kPa, and the coating prepared in Example 2 has an ice adhesion strength of ~43 kPa, indicating that the transparent self-lubricating anti-icing coatings prepared in Examples 1 and 2 have extremely strong anti-icing properties.
[0069] The surface of the transparent self-lubricating anti-icing coating prepared in Example 1 was abraded 200 times under a load of 250 g to examine the change in ice adhesion on the coating surface before and after abrasion. The results are as follows: Figure 7 As shown. Figure 7 It can be seen that after wear (250g load, 200 wears), the coating can still maintain an ice adhesion strength of ~42kPa. The increase in ice adhesion strength is not large and can still meet the anti-icing requirements.
[0070] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a transparent self-lubricating anti-icing coating, characterized in that: The following steps are involved: (1) mixing an acrylate monomer, an acrylate self-lubricating component, an initiator and an organic solvent to obtain a dispersion; the acrylate monomer is one or more of isobornyl methacrylate, hydroxyethyl methacrylate, isopropenyl acetate, ethyl acrylate, lauryl acrylate, octadecyl acrylate and butyl methacrylate; the acrylate self-lubricating component is one or more of lauryl methacrylate and octadecyl methacrylate; the mass of the acrylate self-lubricating component in step (1) is 5 to 85% of the sum of the mass of the acrylate monomer and the acrylate self-lubricating component; the mass of the initiator is 0.5 to 5% of the sum of the mass of the acrylate monomer and the acrylate self-lubricating component; (2) heating the dispersion to perform a polymerization reaction to obtain a self-lubricating resin dispersion; (3) mixing the self-lubricating resin dispersion with a high-strength resin component and a curing agent to obtain a mixed dispersion; the high-strength resin component is one or more of epoxy resin, polydimethylsiloxane, polyurethane and polyurea; based on the total mass of the acrylate monomer, the acrylate self-lubricating component, the high-strength resin component and the curing agent, the total mass percentage of the acrylate monomer and the acrylate self-lubricating component is 10 to 90%; (4) coating the mixed dispersion on the surface of a substrate and curing the mixed dispersion to form the transparent self-lubricating anti-icing coating.
2. The preparation method according to claim 1, characterized in that: The polymerization reaction temperature in step (2) is 50-120° C. and the reaction time is 8-12 hours.
3. The preparation method according to claim 1, characterized in that: The substrate in step (4) includes glass, wind turbine blades, photovoltaic panels, epoxy resin boards, metals or wood.
4. A transparent self-lubricating anti-icing coating prepared by the preparation method according to any one of claims 1 to 3, wherein the transparent self-lubricating anti-icing coating comprises a high-strength resin and a self-lubricating resin, and the molecular chains of the high-strength resin and the self-lubricating resin form an interpenetrating network structure.
Citation Information
Patent Citations
Nanocomposite ice-coating-proof paint having properties of superhydrophobicity and low adhesive strength
CN102660182A
Transparent high-strength ice-dredging coating as well as preparation method and application thereof
CN115141538A